Microwave Assisted Synthesis of 1,2,4-Triazolo[4,3-a]perimidines - Davoodnia, A.; Saeidi, A.; Tavakoli-Hoseini, N. (Asian Journal of Chemistry, 2012)
Microwave assisted synthesis of some 1,2,4-triazolo[4,3-a]perimidines through cyclocondensation reaction of 2-hydrazino-1H-perimidine with triethylorthoesters or aryl nitriles in solvent-free conditions is described. The present methodology offers several advantages, such as a simple procedure with an easy work-up, short reaction times, high yields and the absence of any volatile and hazardous organic solvents.